2005
DOI: 10.1128/iai.73.3.1625-1634.2005
|View full text |Cite
|
Sign up to set email alerts
|

Monocytes Are Highly Sensitive toClostridium difficileToxin A-Induced Apoptotic and Nonapoptotic Cell Death

Abstract: In this study we investigated the in vitro responses of peripheral blood mononuclear preparations and purified monocytes to Clostridium difficile toxin A. In contrast to the responses of T and B cells, exposure to toxin A led to a rapid loss of monocytes in a time-and dose-dependent fashion (the majority of cells were lost within 24 h of exposure to >100 ng of toxin per ml). Transmission electron microscopy, flow cytometry, and fluorescence microscopy after propidium iodide and Hoechst staining showed that cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
34
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(39 citation statements)
references
References 53 publications
2
34
0
Order By: Relevance
“…TcdA has also been shown to directly bind and induce apoptosis in monocytes, thereby inactivating key effector cells and directly influencing the host protective immune response [Modi et al 2011;Solomon et al 2005].…”
Section: Clostridium Difficile Virulence Factorsmentioning
confidence: 99%
“…TcdA has also been shown to directly bind and induce apoptosis in monocytes, thereby inactivating key effector cells and directly influencing the host protective immune response [Modi et al 2011;Solomon et al 2005].…”
Section: Clostridium Difficile Virulence Factorsmentioning
confidence: 99%
“…Indeed, our previous studies have shown that among the normal human colonic mucosal cells, epithelial cells and macrophages (and also monocytes) are more sensitive than lymphocytes to toxin A-induced cell death (25,26,42). Although direct comparisons have not been Compared to myofibroblasts cultured in control medium (0 g/ml) for the relevant periods, there were significant reductions in mitochondrial dehydrogenase activity in cells exposed to 0.1 g/ml toxin B for 72 h and to 1 and 10 g/ml toxin B for 24 h, 48 h, and 72 h. ϩ, P Ͻ 0.02; * , P Ͻ 0.0001.…”
Section: Discussionmentioning
confidence: 99%
“…The nuclear morphologies of control and toxin-exposed myofibroblasts were studied by fluorescence microscopy after staining with Hoechst 33342 dye (42). Immunohistochemical studies were undertaken using monoclonal antibodies to alpha-smooth muscle actin, desmin, and vimentin (all from Sigma).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…These recruit circulating inflammatory cells such as neutrophils into the site of infection and perpetuate the inflammation and fluid secretion associated with CDI (Pothoulakis, 2000). In addition to the indirect effect of the toxins on cells of the immune system, C. difficile toxin A has also been shown to directly bind to peripheral blood mononuclear cells, most notably monocytes and induce cell death by apoptosis (Modi et al, 2011;Solomon et al, 2005). This highlights the essential role that toxins play in initiating and prolonging bacterial infection by inactivating key elements of the host protective immune response.…”
mentioning
confidence: 99%